2018
DOI: 10.20882/adicciones.897
|View full text |Cite
|
Sign up to set email alerts
|

Uso de reducción de daños y gravedad psicopatológica y médica en pacientes en programa de mantenimiento con metadona

Abstract: In conclusion, MMP-HRP patients are younger compared to MMP-NO HRP patients, they also receive higher doses of methadone and had more intravenous use. The above findings imply that the early onset of high risk drug use and long-term exposure to heroin have more severe outcomes such as higher comorbidities (e.g. infectious diseases, medical and psychiatric disorders), and consequently, these patients are a more vulnerable group with a worse prognosis.Keywords: harm reduction program; methadone maintenance treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
2
0
4
Order By: Relevance
“…For example, results from our descriptive analyses indicated that nearly 60% of OUD treatment participants also had a dual mental health diagnosis in the past year. This finding was expected and aligns with previous reports that dual mental health and psychiatric disorders are exceptionally high among individuals with OUD [47,48]. Importantly, additional research has pointed to the intersectional relationships between mental health problems, MMT utilization, and the experience of social inequities, in particular among MMT patients who also struggle with mental health diagnoses [49].…”
Section: Discussionsupporting
confidence: 89%
“…For example, results from our descriptive analyses indicated that nearly 60% of OUD treatment participants also had a dual mental health diagnosis in the past year. This finding was expected and aligns with previous reports that dual mental health and psychiatric disorders are exceptionally high among individuals with OUD [47,48]. Importantly, additional research has pointed to the intersectional relationships between mental health problems, MMT utilization, and the experience of social inequities, in particular among MMT patients who also struggle with mental health diagnoses [49].…”
Section: Discussionsupporting
confidence: 89%
“…Also, thanks to the implementation of the program, 17 new patients have been identified who, after the program ended, have been integrated with the community mental health services via referrals to their mental health teams and the addictive disorders unit and other resources in the addiction care network (outpatient drug clinics and therapeutic communities) (Volkow, 2020), which leads to their reincorporation to society, as it has been proposed (Fazel et al, 2014). There are previous experiences which suggest that damage reduction programs and low threshold programs are useful to supply patients with basic resources which could be an entry point to the general and mental health care system (Martínez-Luna et al, 2018) and are well perceived by the patients, some of them in a vulnerable situation or homeless (Daigre et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a los programas de PMM en usuarios de drogas por vía parenteral, son estadísticamente más frecuentes en malos adherentes en el análisis bruto, pero no resulta significativa esta asociación en el análisis multivariante. Este hallazgo difiere de los sugerido por otros autores (Malta, Strathdee, Magnanini y Bastos, 2008), y podría deberse a que, en nuestra muestra, el perfil de paciente en PMM se corresponde con un peor nivel socioeconómico y situación clínica, lo cual sería congruente con los hallazgos de otros estudios (Martínez-Luna et al, 2018;Pedrero-Pérez y Grupo MethaQoL, 2017).…”
Section: Discussionunclassified